Determinants of Social-economic Mobility in the Northern Region of Malaysia - Mat, Siti Hadijah Che; Harun, Mukaramah; Bakar, Nor’Aznin Abu (International Journal of Economics and Financial Issues, 2016)
Colleting the data through a survey in the Northern region of Malaysia; Kedah, Perlis, Penang and Perak, this study investigates intergenerational social mobility in Malaysia. We measure and analyzed the factors that influence social-economic mobility by using binary choice model (logit model). Social mobility can be measured in several ways, by income, education, occupation or social class. More often, economic research has focused on some measure of income. Social mobility variable is measured using the difference between educational achievement between a father and son. If there is a change of at least of two educational levels between a father and son, then this study will assign the value one (1) which means that social mobility has occurred. We found that besides father’s education, father’s attitude and the establishment of a university in the area have also contributed to social mobility of the rural communities. Keywords: Social-Economic Mobility; Malaysia, logit model JEL Classifications: O100, O180